Sarcoidosis vs. Colon Cancer Metastasis: Diagnostic Dilemma and the Role of PET Scan in Monitoring Disease Activity - Mahmood, Raai; Al Banaa, Kadhim; Ibrahim, Israa; Hashim, Ahmed; Torregrosa, Luis (Case Reports in Rheumatology, 2021)
Sarcoidosis is a systemic inflammatory disorder characterized by “noncaseating granulomas.” It primarily affects the lungs, but multiple other organs can be involved. Sarcoidosis has been increasingly reported in association with cancer. It can precede, follow or occur at the same time as the diagnosis of cancer. We report a case of sarcoidosis that was diagnosed concomitantly with colon cancer, highlighting the diagnostic dilemma of sarcoidosis vs. cancer metastasis, the relationship between the two, and the value of PET scan in follow-up and monitoring of disease activity.